2004
DOI: 10.1677/joe.1.05838
|View full text |Cite
|
Sign up to set email alerts
|

Screening of six risk exons of the RET proto-oncogene in families with medullary thyroid carcinoma in the Czech Republic

Abstract: Medullary thyroid carcinoma (MTC) occurs as a sporadic form (75%) or as an autosomal dominant inherited familial disorder (25%) called familial MTC (FMTC) or as multiple endocrine neoplasia type 2 (MEN2) syndromes. Germ-line mutations in the rearranged during transfection (RET) proto-oncogene in exons 10, 11, 13, 14, 15 and 16 are known to be a cause of most of the familial forms. In this paper we report molecular genetic testing of 106 families with MTC (358 tested persons) from the Czech Republic in which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
(42 reference statements)
3
31
1
3
Order By: Relevance
“…Table 2 The spectrum of RET mutations identified in families with hereditary medullary thyroid cancer in our center in Greece compared with those described by other European groups. The prevalence (n(%)) of each mutation is shown (data from references (8,20,22) Declaration of interest The authors declare that there is no conflict of interest that could be perceived as prejudicing the impartiality of the research reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 The spectrum of RET mutations identified in families with hereditary medullary thyroid cancer in our center in Greece compared with those described by other European groups. The prevalence (n(%)) of each mutation is shown (data from references (8,20,22) Declaration of interest The authors declare that there is no conflict of interest that could be perceived as prejudicing the impartiality of the research reported.…”
Section: Discussionmentioning
confidence: 99%
“…the Czech Republic they represent 21.7% (23/106) of MTC patients (20,25). The relevant percentage in Spain is 22.8% (26/114) (22).…”
Section: European Journal Of Endocrinologymentioning
confidence: 96%
See 1 more Smart Citation
“…Sequencing was performed in an ABI3100 genetic analyzer. The genetic protocol included the screening for RET mutations in exons 7-19 and 21, according to standard procedures (10)(11)(12)(13)(14).…”
Section: Genetic Analysismentioning
confidence: 99%
“…MEN2 is caused by germline gain-of-function mutations of the RET proto-oncogene (RET) (2). Mutations affecting the cysteine-rich extracellular domain encoded in RET exons 10-15 have been associated with MEN2A; a single point mutation in RET exons 15 and 16 has been associated with MEN2B; mutations at certain codons in various exons of RET (5,8,(11)(12)(13)(14)(15)(16) have been associated with familial medullary thyroid carcinoma (FMTC) (1,(3)(4)(5)(6)(7). However, the G533C mutation in exon 8 of the RET is a rare mutation and has been mainly associated with FMTC (8).…”
Section: Introductionmentioning
confidence: 99%